Towards a parallel hybrid highly accurate Navier-Stokes solver - Borchers, Wolfgang; Kräutle, Serge; Pasquetti, Richard; Rautmann, Reimund; Roß, N.; Wielage, Kerstin; Xu, Chuanju (Numerical Flow Simulation II, 2001)
This paper presents the last progresses obtained in the development of a parallel multidomain/multi-method Navier-Stokes solver. Three points are addressed: (i) the preconditioning of the iterative procedure which results from using a multi-domain approach, (ii) the semi-Lagrangian method to be used for the transport step and (iii) the first results obtained with finite difference/finite element - spectral Chebyshev couplings.